The concept of intelligent gamification, virtual reality & artificial intelligence (AI) to face the pandemic in education - Wibowo, Sasono; Gamayanto, Indra; Arifin, Zaenal (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2024)
When facing a pandemic, education experienced a considerable surprise, where many things made us not expect this to happen. This results in several problems, such as educational institutions needing more time to be ready when facing the cessation of the teaching and learning process, information technology infrastructure suddenly being used to its maximum capacity, and human resources, which in some educational institutions may not be ready. In this research, we will use innovation profiling to implement pandemic learning systems in 2024. If it happens again, this framework will help us see the big picture when dealing with a pandemic. This research results from the 2024 pandemic learning systems framework, in which stages for overcoming the pandemic significantly influence the teaching and learning process in education. Therefore, we need to increase our readiness to face all of this. It is essential to do so that the teaching and learning process will continue to run well and by the learning outcomes set by each institution.